THE IMPACT OF ROLE-PLAY ON STUDENTS' SPEAKING PERFORMANCE - KHASBANI, IMAM; SELI, FENNY YUTIKA (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2021)
Speaking has been widely regarded as the core element of English language learning. The success of students in learning English is often measured by how well and articulates they can express themselves orally. Despite its popularity and the fact that it becomes one of the most embraced language skills by educational practitioners inside the classroom, speaking has been and is still thought of as the most challenging skill to master. A number of teaching techniques have been invented to tackle this issue and among them is role-play. Relying on this situation, the present study seeks to reveal the possible impact of role-play on students' oral performance and speaking confidence. Preliminary and post-tests as well as questionnaires were employed during the study for the purpose of data collections. The analysis of the collected data suggests an improvement in the participants' speaking ability in the experimental group, indicated by an increase in their average score on the speaking test from 66.50 to 76.28. This score improvement appears to be higher than the control groups, whose average score moved from 67.29 to 71.76. In addition to that, the investigation on the collected data also shows that role-play had a significant effect on the establishment of positive interaction with both high and low speaking confidence participants in the experimental group. There was an improvement in speaking performance scores from 69.70 to 78.29 and 50.50 to 68.80 from high and low speaking confidence participants. The improvement witnessed in the experimental class also appears to be more significant than that of the control group, whose scores changed from 70.25 to 74.10 for high speaking confidence participants and from 52.50 to 59.20 for the participants with low speaking confidence. The results of the study indicate that role-play plays a prominent part in improving students' speaking performance.